The management of developmental dysplasia of the hip in children aged under three months: a consensus study from the British Society for Children's Orthopaedic Surgery. (1st February 2023) - Aarvold, Alexander; Perry, Daniel C.; Mavrotas, Jason; Theologis, Tim; Katchburian, Marcos; ,
Abstract : Aims: A national screening programme has existed in the UK for the diagnosis of developmental dysplasia of the hip (DDH) since 1969. However, every aspect of screening and treatment remains controversial. Screening programmes throughout the world vary enormously, and in the UK there is significant variation in screening practice and treatment pathways. We report the results of an attempt by the British Society for Children's Orthopaedic Surgery (BSCOS) to identify a nationwide consensus for the management of DDH in order to unify treatment and suggest an approach for screening. Methods: A Delphi consensus study was performed among the membership of BSCOS. Statements were generated by a steering group regarding aspects of the management of DDH in children aged under three months, namely screening and surveillance (15 questions), the technique of ultrasound scanning (eight questions), the initiation of treatment (19 questions), care during treatment with a splint (ten questions), and on quality, governance, and research (eight questions). A two-round Delphi process was used and a consensus document was produced at the final meeting of the steering group. Results: A total of 60 statements were graded by 128 clinicians in the first round and 132 in the second round. Consensus was reached on 30 out of 60 statements in the first round and an additional 12 in the seond. This was summarized in a consensus statement and distilled into a flowchart to guide clinical practice. Conclusion: We identified agreement in an area of medicine that has a long history of controversy and varied practice. None of the areas of consensus are based on high-quality evidence. This document is thus a framework to guide clinical practice and on which high-quality clinical trials can be developed. Cite this article: Bone Joint J  2023;105-B(2):209–214.